2007
DOI: 10.1002/pd.1793
|View full text |Cite
|
Sign up to set email alerts
|

Dose dependency between cigarette consumption and reduced maternal serum PAPP‐A levels at 11–13+6 weeks of gestation

Abstract: In first-trimester screening for Down syndrome by maternal serum PAPP-A and free beta-hCG the impact of correcting for the dose dependant rather than the all or nil effect of smoking is marginal. However, a dose dependent correction improves the accuracy of the individual patient-specific risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 27 publications
0
24
0
1
Order By: Relevance
“…Several studies have also shown a higher false-positive rate for the trisomy 21 risk when disregarding the correction of the maternal smoking status [16,17] . A recently published study describes a direct dose-dependency between smoking and lower PAPP-A values [18] . The fetal NT does not seem to be influenced by the smoking status of the mother [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also shown a higher false-positive rate for the trisomy 21 risk when disregarding the correction of the maternal smoking status [16,17] . A recently published study describes a direct dose-dependency between smoking and lower PAPP-A values [18] . The fetal NT does not seem to be influenced by the smoking status of the mother [17] .…”
Section: Discussionmentioning
confidence: 99%
“…We found that mean and median NT increased with increasing daily cigarette consumption. Kagan et al [2] recently investigated the impact of correcting the biochemical markers for the dose effect of smoking rather than the 'all or nil' effect, and concluded that correction made only marginal improvement on overall screening performance. Another argument for using smoking status defined as smoking versus nonsmoking is that information on daily cigarette consumption may not be reliable in pregnant women, as this information is self-reported and women may tend to underreport the daily consumption.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, PAPP-A concentrations expressed in IU/l as well as in MoM were significantly lower in the smoking group in each trimester of pregnancy. Also a dose-related PAPP-A/cigarette smoking relationship has been found in a few studies [22, 23, 29, 37]. Some authors have observed a significant negative correlation between maternal PAPP-A levels in the first trimester and the number of cigarettes smoked per day [29].…”
Section: Discussionmentioning
confidence: 94%
“…It may result in inadequate expression of PAPP-A and IGF axis disorders, reduced active transport of essential nutrients to the fetus, and lead to disturbances of embryogenesis and in consequence fetal growth [14, 35]. It is widely accepted that serum concentrations of PAPP-A in smoking pregnant women in the first trimester are 15–25% lower than those observed in tobacco-abstinent groups [8, 9, 24, 27, 29, 32, 36], but only Spencer and Covans [23] have examined the level of this protein in the second trimester of pregnancy. The authors found a small but significant decrease of 10% in the PAPP-A MoM of smokers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation